Cross-Cultural and Toponymy Course for History Teachers in East Java: Dissemination Recent Study about Singhasari Kingdom in History Learning - Wahyudi, Deny Yudo; Jati, Slamet Sujud Purnawan; Wijaya, Daya Negri; Laili, Vita Sabrina Azda; Ananda, Labuda Shofiya; Ikhrom, Anisa Musyaroful (Journal of Social Knowledge Education (JSKE), 2025)
Purpose of the study: Introducing and ptimalizing the results of cross-cultural studies and toponymic approaches in history education as an effort to improve the competence of history teachers. Specifically, to connect local historical sites in classroom learning, and to respond the requirements of the Merdeka Curriculum in providing essential, relevant, and in-depth learning materials. Methodology: This study employed a qualitative descriptive approach with elements of development research. The implementation of the service is based on specific stages, namely 1) observation and preliminary studies, 2) recommendations for activities, 3) curriculum design and special tools, 4) course implementation, 5) evaluation of activities, and 6) plans for sustainable activities. Main Findings: The result of this community service activity is the improvement of teachers' abilities to utilize local potential, especially in the use of local historical sites through a toponymic approach and cross-cultural Nusantara. Novelty/Originality of this study: The integration of cross-cultural and toponymy approaches is an interesting and rare offering in teacher professional development. This is especially in the utilization of local historical sites as medium for contextual learning media in response to the challenges of a curriculum based on local history.